Optimizing a Hydrogen and Methane Blending System Through Design and Simulation - Ştefan Ionuţ Spiridon; Bogdan Florian Monea; Eusebiu Ilarian Ionete (Fuels, 2025)
Hydrogen–methane gas mixtures are increasingly recognized as a viable path toward achieving carbon neutrality, leveraging existing natural gas infrastructure while reducing greenhouse gas emissions. This study investigates a novel static mixing device designed for blending hydrogen and methane, employing both experimental tests and three-dimensional computational fluid dynamics (CFD) simulations. Hydrogen was introduced into a methane flow via direct injection, with experimental mixtures ranging from 5% to 18% hydrogen. The mixture quality was assessed using a specialized gas chromatograph, and the results were compared against simulated data to evaluate the mixer’s performance and the model’s accuracy. The system demonstrated effective blending, maintaining uniform hydrogen concentrations across the outlet with minimal variations. Experimental and simulated results showed strong agreement, with an average accuracy error below 2%, validating the reliability of the CFD model. Smaller nozzles (0.4 mm) achieved greater mixing uniformity, while larger nozzles (0.6 mm) facilitated higher hydrogen throughput, indicating trade-offs between mixing precision and flow capacity. The mixing device proved compatible with existing pipeline infrastructure, offering a scalable solution for hydrogen integration into natural gas networks. These findings underscore the mixer’s potential as a practical component in advancing the hydrogen economy and achieving sustainable energy transitions.